2006
DOI: 10.1038/sj.npp.1301261
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Evoked Glutamate Release by Neurosteroid Allopregnanolone Via Inhibition of L-Type Calcium Channels in Rat Medial Prefrontal Cortex

Abstract: Allopregnanolone is one of the most important neurosteroids in the brain. We studied the effect and mechanism of allopregnanolone on spontaneous and evoked glutamate release in the medial prefrontal cortex using electrophysiological and biochemical methods combined with pharmacological approaches. The results showed that allopregnanolone had no effects on the frequency of miniature excitatory postsynaptic current (mEPSCs), but inhibited the depolarizing agent veratridine-evoked increase in the frequency of spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Notably, effects in human microglia could be blocked via L-type Ca 2+ channel inhibition (Hegg et al, 2000). AlloP may exert similar effects to regulate [Ca 2+ ] i and has been shown to dampen glutamatergic activity in mPFC via inhibition of L-type Ca 2+ channels (Hu et al, 2007). In particular, Ca v 1.2 and Ca v 1.3 L-type channels are identified as targets of AlloP inhibition (Earl & Tietz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, effects in human microglia could be blocked via L-type Ca 2+ channel inhibition (Hegg et al, 2000). AlloP may exert similar effects to regulate [Ca 2+ ] i and has been shown to dampen glutamatergic activity in mPFC via inhibition of L-type Ca 2+ channels (Hu et al, 2007). In particular, Ca v 1.2 and Ca v 1.3 L-type channels are identified as targets of AlloP inhibition (Earl & Tietz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the PFC, the progesterone metabolite allopregnanolone inhibits dopamine induced glutamate release ( 90 ), a mechanism that may be of special importance in relating the effects of progesterone to cognition and neuropsychiatric diseases ( 91 ). Allopregnanolone also inhibits glutamate release through an inhibition of the L-type Calcium channel ( 92 ). It has been observed that allopregnanolone, through the potentiation of GABAergic synapses, leads to a decrease in glutamate receptor efficiency ( 93 , 94 ).…”
Section: Hormone Actions In the Female Brainmentioning
confidence: 99%
“…Contrary, another Preg derivative – allopregnanolone, was reported to reduce PKA activation (a necessary upstream event) and presynaptic glutamate release in rat medial prefrontal cortex [ 110 ]. This was verified by using L-type calcium channel antagonists, verapamil and nimodipine, which blocked the effect of allopregnanolone.…”
Section: Calcium and Neurosteroidsmentioning
confidence: 99%